Hemodynamic and Homeostasis Changes after Continuous Renal Replacement Therapy in Septic Shock Children at Vietnam National Children’s Hospital - Duy Phuc, Tong; Ba Dung, Tran; Viet Hung, Dau; Anh Tuan, Ta; Quang Quan, Thieu; Huu Phuc, Phan (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 3, 2023)
Objectives: This study aims to describe changes in hemodynamics and homeostasis after continuous renal replacement therapy (CRRT) in septic shock children without acute kidney injury. Methods: An observational study was conducted in the pediatric intensive care unit (PICU) at Vietnam National Children’s Hospital from January 2018 to June 2022. Children aged under 18 years old with septic shock and without acute kidney injury who required CRRT were analyzed on demographic factors, baseline clinical and laboratory results, changes in hemodynamics and homeostasis at 6 hours, 12 hours, 24 hours, 48 hours, 72 hours, 4 days and 5 days after CRRT initiation. Results: A total of 125 children (male, 57.6%) were enrolled in the study. The median age was 11.5 months (IQR: 5 – 29). Overall PICU mortality rate at day 28 was 40.8%. Among survivors, there was a statistically significant improvement in heart rate, mean blood pressure, vasoactive inotropic score (VIS), and pH at all mentioned periods after CRRT initiation. Lactatemia statistically significantly decreased after 24 hours of CRRT initiation (p < 0.05). Among non-survivors, there was a statistically significant improvement in heart rate at all the periods and in mean blood pressure at 6 hours and 12 hours, while there was no improvement in VIS, pH, and lactatemia. Conclusion: CRRT played an important role in stabilizing hemodynamics and homeostasis in septic shock children without acute kidney injury.